Cassava field guide - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
'Cassava' by Pierre Silvestre, translated from the French by Paul Skinner, CTA and Macmillan Publishers Ltd, The Tropical Agriculturalist series, 1989, 82pp, ISBN 0 333 47395 7. Available from CTA.